Impact of dietary intervention on eating behavior after ischemic stroke - Besseau, Samuel; Sartori, Eric; Larnier, Pauline; Paillard, François; Laviolle, Bruno; Mahé, Guillaume (Frontiers in Nutrition, 2023)
Objective Ischemic stroke is a major health issue. Currently, the relationship between dietary patterns and the occurrence of cardiovascular diseases including stroke is established, but the effect of systematic dietary intervention on dietary changes in ischemic stroke patients is unknown. Our objective was to compare changes in the dietary pattern of ischemic stroke patients who received a systematic diet intervention with changes in the dietary pattern of ischemic stroke patients who did not receive a systematic dietary intervention during their hospitalization. Methods In this before-and-after study, two groups of patients with ischemic stroke were compared: Group 1 included 34 patients admitted with an ischemic stroke without a systematic dietray intervention; Group 2 included 34 patients admitted with an ischemic stroke with a systematic dietary intervention. Dietary patterns were assessed by a validated food frequency questionnaire of 19 questions (from a previously validated questionnaire of 14 questions), at the onset of stroke and at 6 months after stroke. This questionnaire allows the calculation of different scores as follows: global food score, saturated fatty acids score (SFA), unsaturated fatty acids score (UFA), fruit and vegetable score, and alcohol score. Results Score changes were more important in group 2 than in group 1 for the global food score (7.4 ± 7 vs. 1.9 ± 6.7, p = 0.0013), the fruit and vegetable score (2 ± 2.6 vs. 0.6 ± 2.2, p = 0.0047), and the UFA score (1.8 ± 2.7 vs. 0.1 ± 3.3, p = 0.0238), whereas no significant differences were observed for the SFA score (−3.9 ± 4.9 vs. −1.6 ± 6, p = 0.1779) and the alcohol score (−0.4 ± 1.5 vs. −0.3 ± 1.1, p = 0.6960). Conclusion This study showed that systematic dietary intervention during hospitalization improves the dietary patterns of ischemic stroke patients. The impact on the recurrence of ischemic stroke or cardiovascular events after dietary pattern changes needs to be studied.